Bojonegoro Regent’s Leadership: Role in Development Transformation Effort - Denny Iswanto; Ringga Ananta Putra (University of Merdeka Malang, 2024)
Development transformation is a strategic endeavor aimed at achieving substantial and enduring changes within a region. In this context, the role of a regional head, particularly one with goodwill, becomes crucial in influencing the progress and outcomes of regional development. This study delves into the impact of a regional head’s goodwill on the development transformation in Bojonegoro Regency. The primary objective of this research is to scrutinize the influence of the regional head’s goodwill on the development transformation in Bojonegoro Regency. The methodology employed in this study is a qualitative approach, supplemented by secondary data analysis techniques. The findings of the study reveal that regional heads with goodwill have the capacity to formulate clear and inspiring visions for the development of Bojonegoro Regency. Their goodwill has spurred them to design progressive policies and programs that are oriented towards community empowerment and leverage technology. Development efforts have been initiated in various sectors, including the internal bureaucracy, public goods provision, social development, and human resources. These sectors have been identified as the leading sectors in the region’s development transformation. However, the study concludes with a note of caution. While development has been primarily focused on the leading sectors, it is essential to broaden the scope of development to other sectors as well. This expansion is crucial to ensure a balanced and inclusive development transformation in Bojonegoro Regency. The study underscores the importance of a regional head’s goodwill in shaping the region’s development trajectory and offers insights for future policy planning.